Enhancing Better Attitude and Achievement in Mathematics Teaching and Learning Through Task-oriented Approach - Akinwamide , Comfort Oluwasesan (International Journal of Educational Management, 2025)
The study investigated the effects of Task-Oriented teaching strategy on the attitude and achievement of students in Mathematics in secondary schools. The study adopted quasi-experimental research design of the pre-test, post-test control group design. The population comprised all Senior Secondary School II students in public secondary schools in Ekiti State. The sample consisted of 160 Senior Secondary School students purposively selected from four public secondary schools in Ekiti State. Two hypotheses were generated. The instruments used to collect data were Mathematics Achievement Test (MAT) and Students' Attitude Towards Mathematics Questionnaire (SATMQJ. The instruments were validated and the reliability coefficients of the instruments were 0. 76 and 0.81 respectively. Hypotheses were tested at 0. 05 level of significance using Analysis of Covariance (ANCOVA). The result of the study revealed that there was significant difference between the pre-test and post-test scores of the students in the experimental group, while the pre-test and post-test scores of the control group showed nesignificant difference. It was found that there was significant difference in the post-tesi of the experimental and control groups. The results showed that Task-Oriented strategy improves students' attitude towards Mathematics. It also enhances achievement in the learning of Mathematics than conventional strategy. Task-Oriented strategy was found to be highly effective in improving students' behaviour during Mathematics classes. Based on the findings of the study, it was recommended that, students should be given tasks and also be opportune to generate and solve tasks that will lead to the discovery of new ideas. Curriculum planners should encourage and support the implementation of Task Oriented strategy of learning. Teachers should be encouraged to use Task-Oriented strategy during classroom interaction.